Penegakan Hukum Terhadap Warga Negara Asing yang tidak Melaporkan Perubahan Status Sipil ke Kantor Imigrasi Kelas II Non Tempat Pemeriksaan Imigrasi Agam - Putri, Aldila; Zulfiko, Riki (Universitas Medan Area, 2025)
The purpose of this study is to discuss the law enforcement against immigration violations in the area of the Class II Non-TPI Immigration Office in Agam and the factors that hinder law enforcement against immigration violations. The method used in this research is descriptive with an empirical juridical type of research, using a qualitative approach. The data was obtained through interviews with the Head of the Intelligence and Immigration Enforcement Section (INTELDAKIM) at the Class II Non-TPI Immigration Office in Agam. The research findings indicate that there are difficulties faced by the INTELDAKIM division in processing law enforcement against violations committed by foreign nationals. These difficulties include a lack of personnel in the INTELDAKIM division to handle the cases, as one of the members is currently undergoing training as an investigator, which creates an imbalance between law enforcement and the number of foreign nationals entering the jurisdiction of the Class II Non-TPI Immigration Office in Agam. Another challenge is the lack of public attention in reporting violations committed by foreign nationals